LAND CONFLICT AND IMPACT ON TOLL ROAD DEVELOPMENT FOR PUBLIC BENEFIT IN SOUTH LAMPUNG REGENCY - Novriwan Hakim, Muhamad Galank; Martinouva, Rissa Afni (Progressive Law Review, 2021)
The development of the Trans Sumatera toll road for the Bakauheni Terbanggi Besar Section II package currently causes uncertainty in the calculation of compensation for residual lands, so that there is a change in the function of the land from the remaining land affected by the development. The remaining land referred to in this study is the rest of the land that has been compensated by agencies that need land, in this case the Ministry of Public Works and Public Housing but still leaves problems that have not been resolved. The problem in this study relates to the basis and process of settlement of compensation for the residual land that has lost its social function and economic value in the construction of the JTTS Bakauheni-Terbanggi Besar Section, efforts that must be undertaken by the community for the remaining land that loses social function and economic value in the JTTS development Large Bakauheni-Terbanggi Section. This research is a normative and empirical juridical research. This research was conducted in Serdang Village, tanjung Bintang District, South Lampung Regency.